2001
DOI: 10.1002/1097-0045(20010215)46:3<200::aid-pros1024>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Intra-prostatic vasculature studies: Can they predict the outcome of transurethral microwave thermotherapy for the management of bladder outflow obstruction?

Abstract: Background Blood perfusion regulates intraprostatic temperatures during transurethral microwave thermotherapy (TUMT). We evaluated baseline intraprostatic vasculature, as a predictor of efficacy of TUMT. Methods Twenty‐two patients, with lower urinary tract symptoms (LUTS) suggestive of bladder outflow obstruction, were treated with TUMT (Prostatron). At baseline, three‐dimensional contrast‐enhanced power‐flow‐Doppler prostate ultrasonography (3D‐CE‐PFD) was performed. Assuming that the percentage of perfused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Prostate tissue exhibits a wide biological variability and several investigators have attempted to identify factors which may have a potential influence on microwave treatment. Floratos et al [1] performed a quantitative estimation of intraprostatic blood flow in patients before thermotherapy, using contrast medium-enhanced power-flow Doppler ultrasonography. Their study failed to show baseline vascularization to be a predictor of the outcome of thermotherapy and this result tallies with the findings obtained in this paper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prostate tissue exhibits a wide biological variability and several investigators have attempted to identify factors which may have a potential influence on microwave treatment. Floratos et al [1] performed a quantitative estimation of intraprostatic blood flow in patients before thermotherapy, using contrast medium-enhanced power-flow Doppler ultrasonography. Their study failed to show baseline vascularization to be a predictor of the outcome of thermotherapy and this result tallies with the findings obtained in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…However, baseline intraprostatic vascularization as assessed by ultrasonography was not shown to have any impact on the efficacy of TUMT [1]. Differences in the heat sensitivity of epithelial and stromal components of hyperplastic prostate tissue were recently described in histological studies [2].…”
Section: Introductionmentioning
confidence: 96%
“…26 However, these features are only moderately predictive. In addition, Floratos and colleagues 27 showed that baseline intraprostatic vascularity, documented by three-dimensional contrast-enhanced power-flow Doppler studies, has no predictive value for the efficacy of TUMT. It seems that static baseline blood flow does not reflect the dynamic thermoregulatory role of blood flow during treatment.…”
Section: Outcome Predictors and Patient Selectionmentioning
confidence: 99%
“…It seems that static baseline blood flow does not reflect the dynamic thermoregulatory role of blood flow during treatment. 27 Controversial results have been published regarding the effectiveness of baseline prostate specific antigen (PSA) as a predictor of the clinical outcome following HE TUMT. Djavan and associates 28 demonstrated that baseline PSA could identify patients with favorable clinical results after TUMT with the Targis device.…”
Section: Outcome Predictors and Patient Selectionmentioning
confidence: 99%
“…Errors in the reconstruction of the geometry can be reduced, for example, by using the SPOT system (Nucletron BV, Veenendaal, The Netherlands), which provides 3D ultrasound imaging. Three-dimensional power Doppler with contrast agents can reveal angiographic and perfusion data and is currently investigated by Bogers et al (1999), Floratos et al (2001) andKruger Hagen et al (2001). The effective perfusion level as measured by each thermosensor can also be used to estimate a 3D heterogeneous perfusion map.…”
Section: Validation In Individual Patientsmentioning
confidence: 99%